2020
DOI: 10.1183/13993003.00775-2020
|View full text |Cite
|
Sign up to set email alerts
|

A fully automatic deep learning system for COVID-19 diagnostic and prognostic analysis

Abstract: Coronavirus disease 2019 (COVID-19) has spread globally, and medical resources become insufficient in many regions. Fast diagnosis of COVID-19, and finding high-risk patients with worse prognosis for early prevention and medical resources optimisation is important. Here, we proposed a fully automatic deep learning system for COVID-19 diagnostic and prognostic analysis by routinely used computed tomography.We retrospectively collected 5372 patients with computed tomography images from 7 cities or provinces. Fir… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
256
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 428 publications
(260 citation statements)
references
References 28 publications
(39 reference statements)
1
256
0
3
Order By: Relevance
“…CT images were segmented via U-net, then COVNet distinguished between COVID-19 and CAP. Wang [23] proposed a fully automatic deep learning system for COVID-19 diagnosis and prognosis based on CT image analysis. First, they made a DenseNet121-FPN for lung segmentation in chest CT images and the proposed novel COVID-19Net for COVID-19 diagnosis and prognosis.…”
Section: Introductionmentioning
confidence: 99%
“…CT images were segmented via U-net, then COVNet distinguished between COVID-19 and CAP. Wang [23] proposed a fully automatic deep learning system for COVID-19 diagnosis and prognosis based on CT image analysis. First, they made a DenseNet121-FPN for lung segmentation in chest CT images and the proposed novel COVID-19Net for COVID-19 diagnosis and prognosis.…”
Section: Introductionmentioning
confidence: 99%
“…The fact that during inference, suspicious or disputable CT slices selected for analysis by the deep model should have been identified by an expert radiologist from the raw CT volume, might be considered as a limitation since a fully automated diagnosis is not possible. That said, as presented in Table I, the proposed methodology outperforms the current literature (19)(20)(21) in terms of AUC performance. In particular, the deep model proposed by Zhang et al (21) demonstrates similar performance with the present analysis but the examined CT slices were manually segmented on lesion basis before classification (COVID-19 versus common pneumonia versus normal patients).…”
Section: Discussionmentioning
confidence: 64%
“…For Hong Kong, Xu et al [ 61 ] showed deep learning yielded better prediction performance for flu-like diseases than the generalized linear model, the least absolute shrinkage and selection operator model, and the autoregressive integrated moving average (ARIMA) model. Wang et al [ 62 ] found deep learning provided a convenient tool for fast screening COVID-19 and finding potential high-risk patients, which may be helpful for medical resource optimization and early prevention before patients show severe COVID-19 symptoms. Various non-China studies indicate that infectious disease can be predicted more effectively when large amounts of data including weather variables and internet big data are used to predict infectious diseases.…”
Section: Resultsmentioning
confidence: 99%